Weaponizing Water: Israel’s Use of Water as a Tool of Aggression on Gaza in 2023 - Barahmeh, Nourhan (جامعة النجاح الوطنية, 2026)
This thesis examines the weaponization of water in the latest aggression on the Gaza Strip which Israel used as a deliberate and systematic policy of warfare and control. The thesis would be examining this policy by evaluating water weaponization's legality under international humanitarian law (IHL), international human rights law (IHRL), and international criminal law. The thesis will address a main question, which is to what extent do Israeli practices targeting Gaza’s water infrastructure constitute violations of international law, and could they amount to international crimes such as war crimes or genocide? The thesis will also examine how the systematic deprivation of access to water through the destruction of infrastructure, and the deprivation of fuel and electricity, and the obstruction of humanitarian aid, all together, can affect the survival and dignity of civilians. It also seeks to determine the scope of Israel’s obligations as an occupying power and whether such practices breach the prohibitions on collective punishment and the protection of essential civilian resources. The thesis uses a qualitative legal analysis as it uses both primary legal instruments, such as the Fourth Geneva Convention, the Additional Protocol I, the Rome Statute, and the Genocide Convention, and secondary sources, such as United Nations reports , commentaries, and documentations from NGO's like Oxfam, and Al-Haq. Finally, the findings of the thesis will show that Israel’s actions constitute serious breaches of IHL, particularly Articles 33, 55, and 56 of the Fourth Geneva Convention, and can also amount to war crimes under Article 8 of the Rome Statute, it also argues that water deprivation can lead to the deliberate creation of life-threatening conditions, which could satisfy the elements of genocide under Article II(c) of the Genocide Convention.
استخدام المياه كسلاح: استخدام إسرائيل للمياه كأداة عدوان ضد غزة في 2023